EFFECT OF STYLUS POSITION SHIFTINGS TO ECCENTRICITY AND ROUNDNESS VALUE IN GLASS HEMISPHERE MEASUREMENTS - Kartika, Nadya Larasati; Rahman, Ardi; Nugraha, Asep Ridwan (LIPI Press, Anggota IKAPI, 2017)
In this research, the effect of stylus position shifting to eccentricity on hemisphere roundness measurement is examined in Research Center for Metrology LIPI (RCM-LIPI). The effect would give the acceptance eccentricity value for center adjustment of hemisphere. Least Square Circle (LSC) data fitting and Gaussian filtering were used in data processing. The result showed that until 3,3 µm shifting value with 3,23 µm in eccentricity the roundness values were constant. However, above this value, the roundness value starting to increase significantly and giving an uncertainty contribution to hemisphere measurement.